Evaluasi Kebijakan Pengelolaan Sampah di Kalurahan Condongcatur Kabupaten Sleman Daerah Istimewa Yogtakarta - PAHLEVI, IRFANI REZA; Sugiyanto, Sugiyanto (Journal of Indonesian Rural and Regional Government, 2025)
Waste is an increasingly complex environmental issue due to population growth, urbanization, and changes in consumption patterns. Condongcatur Village, the most populous area in Sleman Regency, faces serious challenges in waste management, particularly in increasing community participation. This study aims to issue a waste management policy in Condongcatur Village based on Sleman Regency Regional Regulation Number 4 of 2015, identify the main obstacles to policy implementation, and develop strengthening strategies to make it more optimal and sustainable. This study uses a qualitative descriptive method with data collection techniques through in-depth interviews, observation, and documentation. Data analysis is carried out through data reduction, data presentation, and drawing conclusions with source triangulation. The results show that the waste management policy in Condongcatur has been implemented through a household waste sorting program, a waste bank, and the management of the 3R TPS. However, the level of community participation is not evenly distributed across the various groups. The main obstacles include limited facilities and infrastructure, weak coordination between stakeholders, and the challenge of institutional poverty in waste management. Based on an evaluation using George C. Edward III's policy implementation model and William N. Dunn's policy evaluation model, the policy was deemed quite effective but not yet optimal. This study recommends strengthening public education, improving supporting facilities, and strengthening the 3R waste management system (TPS 3R) and community-based waste management networks.